Pendidikan Inklusif: Konsep Dasar, Ruang Lingkup, Dan Pembelajaran - Totok Yulianto (Institut Agama Islam Negeri Purwokerto, 2018)
Inclusive education provides educational services based on the variation of learners potential in an educational institution. This service is very suitable for children with special needs that has unique individual characteristics. The implementation of inclusive education is currently not aligned with national schooling systems that tend to implement a standardized service system. The term of standard service is the equal treatments for each individual and the learning completeness with the benchmarks of the national standard. In relation to the condition of children with special needs, who has various limitations and learning needs, the implementation of inclusive education requires curriculum modification, learning strategy, learning assessment system and school management in accordance with the needs for children with special needs.